EFFECTS OF FINANCIAL INCLUSION AND OUT OF POCKETS COST ON HUMAN HEALTH (1990 - 2020) - AKINTUNDE, Temitope Sade; OLADIMEJI, Ifeade Adetutu; ARIBATISE, Adekunle (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
This study examined the dynamic relationship amongst financial inclusion, out of pocket expenditure and health outcome proxied by life expectancy. This was with the view to investigate the effects of financial inclusion and out-of-pocket medical expenses on health outcomes as well as the causal connections between various variables in Nigeria. Time series data from 1990 through 2020 were analysed using Autoregressive Distributed Lag (ARDL) and pairwise granger causality as the estimation technique. The study found a positive relationship between financial inclusion and health outcomes and there was a bidirectional causal relationship between financial inclusion and life expectancy and a unidirectional causal relationship running from out-of-pocket expenditure to life expectancy at 5% significance level and vice versa. The study also revealed that financial inclusion had a positive and significant effect on life expectancy in Nigeria. Also, out of pocket expenditure had revealed not to be statistically significant on life expectancy in the long-run. JEL classification: G21, H51, I31